London - Clarke, Catriona; McKenna, Terry; Lalonde, Tom; Swain, Hedley; Kelly, Alison; Museum of London (London : Usborne Publishing Limited, 2023)
How did London become the big, bustling city it is today? When was the Underground built? What was the Great Fire of London? Where are kings and queens crowned? This engaging book has all the answers and more, with clear photographs, detailed illustrations, informative text and links to carefully chosen websites. Usborne Beginners are exciting books for children who are beginning to read on their own.
Keywords: London (England) -- History -- Juvenile literature; London (England) -- History -- Juvenile works; History